2020
DOI: 10.1093/milmed/usaa032
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of a Shock Absorbing Insole During Military Training in a Group of Soldiers: A Pilot Study

Abstract: Objective Soldiers’ lower limbs and feet are frequently affected by overload- and overuse-related injuries. In order to prevent or limit the incidence of these injuries, the use of foot orthoses is often recommended. The aim of this study is to assess the effects of shock-absorbing insoles on in-shoe plantar pressure magnitude and distribution in a group of professional infantry soldiers wearing military boots during standard indoor military training. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The anchor statements indicating the lowest possible comfort score included ‘not comfortable at all’ [19–22, 25, 26, 30, 39, 49, 50, 53, 55, 56, 61–65, 73, 79, 82–85, 89, 93], ‘very uncomfortable’ [27, 28, 40, 41, 45, 46, 58, 68, 74, 78, 79, 98], ‘least comfortable’ [44, 76, 80, 90], ‘extremely uncomfortable’ [48, 59, 89], ‘not comfortable’ [71, 75], ‘not at all comfortable’ [15, 18], ‘not acceptable’ [37, 70], ‘totally disagree’ [10], ‘least comfortable imaginable’ [35], ‘not satisfactory’ [42], ‘very bad comfort’ [43], ‘very, very low’ [47], ‘minimum comfort’ [69], ‘maximal pain/discomfort’ [99], ‘not very comfortable’ [100], ‘completely uncomfortable’ [104], ‘extremely bad’ [57] and ‘unbearable discomfort’ [87]. The anchor statements indicating the highest possible comfort score included ‘most comfortable imaginable’ [19–22, 25, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The anchor statements indicating the lowest possible comfort score included ‘not comfortable at all’ [19–22, 25, 26, 30, 39, 49, 50, 53, 55, 56, 61–65, 73, 79, 82–85, 89, 93], ‘very uncomfortable’ [27, 28, 40, 41, 45, 46, 58, 68, 74, 78, 79, 98], ‘least comfortable’ [44, 76, 80, 90], ‘extremely uncomfortable’ [48, 59, 89], ‘not comfortable’ [71, 75], ‘not at all comfortable’ [15, 18], ‘not acceptable’ [37, 70], ‘totally disagree’ [10], ‘least comfortable imaginable’ [35], ‘not satisfactory’ [42], ‘very bad comfort’ [43], ‘very, very low’ [47], ‘minimum comfort’ [69], ‘maximal pain/discomfort’ [99], ‘not very comfortable’ [100], ‘completely uncomfortable’ [104], ‘extremely bad’ [57] and ‘unbearable discomfort’ [87]. The anchor statements indicating the highest possible comfort score included ‘most comfortable imaginable’ [19–22, 25, …”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing different insole designs have generally found that softer, more flexible insoles are perceived as more comfortable (in casual footwear [99], running shoes [31, 67, 80] and military footwear [42, 69]). However, comfort perceptions related to insole hardness may vary according to an individual's occupation, as Anderson et al [14] have reported that people standing for long periods at work prefer soft materials under the heel and forefoot but firmer materials under the arch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study results showed that subjects wearing the wrong shoe size reported lower footwear comfort ratings. To potentially increase footwear cushioning and comfort shock-absorbing insoles have been recommended [ 8 , 40 ]. Prefabricated foot orthoses were found to be effective in preventing lower limb overuse injuries [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oh et al [5] have argued that people have difficulty walking with the correct posture when the heel height of the shoe is over 5 cm, which fatigues the foot very easily. Insoles were originally designed and developed to achieve a functional objective to prevent muscle fatigue by distributing body weight and protecting the ankle and knee joints by absorbing impact [6]. However, as more people are becoming interested in appearance, young men often use HH shoes and RHIs to overcome dissatisfaction with their heights and gain confidence regarding their heights [1,7].…”
Section: Introductionmentioning
confidence: 99%